The Academic Motivation and Academic Achievement in Iranian Universities of Medical Sciences: A systematic Review and Meta-Analysis - Dehghan, Fateme (International Journal of Education and Cognitive Sciences, 2022)
Motivation is one of the main factors in learning and it can affect different behavioral aspects of students in academic environment. Academic motivation can be considered as the only factor with direct effect on academic achievement. The present meta-analysis study is an attempt to determine academic motivation and academic achievement based on Vallerand’s scale and Hermans’ questionnaire in students in Iranian universities of medical sciences. The study was carried out as a meta-analysis work on studies published from 2001 to 2018. The relevant studies were searched using keywords “academic motivation” and “academic achievement” in SID, Medline (PubMed), and ScienceDirect. Heterogeneity in the studies was examined using I2 index and data analysis was done in Comprehensive Meta-Analysis software. Out of 16 articles that entered the meta-analysis process; seven articles were based on Vallerand’s scale (AMS) and nine articles were based on Hermans’ questionnaire (AMQ). Mean and standard deviation score of academic motivation based on Vallerand’s scale was 109.9±16.4 and mean and standard deviation score of academic achievement based on Hermans’ questionnaire was 96.83±6.38. The effects of sample size and year of publication were measured based on meta-regression. In terms of sample size, the mean score increased with an increase in sample size in the both Vallerand and Hermans studies. In terms of year of publication, the mean score increased with increase in the year of publication in Vallerand’s studies and decreased in Hermans’ studies (P